2001
DOI: 10.1258/1357633011936255
|View full text |Cite
|
Sign up to set email alerts
|

Telecardiotocography in prenatal telemedicine

Abstract: Fig 1 Example of a computerized cardiotocographic trace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Consequently, this technology may have the potential to reduce the rates of perinatal deaths. Wireless fetal heart monitors that transmit fetal heart rate data to a central server remotely either through modems [14] or Bluetooth [15] have been developed to allow real-time assessment of labour. Pilot studies have found the Bluetooth technology to be acceptable and feasible to both women and clinicians in both outpatient and inpatient settings of developed countries [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this technology may have the potential to reduce the rates of perinatal deaths. Wireless fetal heart monitors that transmit fetal heart rate data to a central server remotely either through modems [14] or Bluetooth [15] have been developed to allow real-time assessment of labour. Pilot studies have found the Bluetooth technology to be acceptable and feasible to both women and clinicians in both outpatient and inpatient settings of developed countries [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in technology have overcome some of these limitations. Standard central units are now often equipped with an interface that stores and subsequently transmits the fetal cardiotocograms via modem allowing remote analysis of fetal cardiotocographs in real time either by central unit screens on inpatient labor wards or on computers equipped with specific software [ 4 ]. These systems still require pregnant women to present to health care facilities equipped with standard monitors.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to assess the agreement in the interpretation of CTG traces between the computerized system 2CTG and experienced and inexperienced observers involved in the first Prenatal Telemedine project started in Italy, based on the 'TOCOMAT' system for conventional and computerized telecardiotocography [12].…”
Section: Introductionmentioning
confidence: 99%